2011
DOI: 10.1007/s11060-011-0741-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea for recurrent surgery and radiation refractory high-grade meningioma

Abstract: Hydroxyurea (HU), an orally administered chemotherapy, has become the de facto standard chemotherapeutic agent in patients with surgically and radiation refractory meningiomas based on a limited literature. A retrospective case series of 35 patients with recurrent WHO Grade 2 (n = 22) or 3 (n = 13) meningioma treated with HU following progression after surgery and radiotherapy was collated with primary study objectives of overall response rate, median and progression free survival (PFS) at 6-months. Thirty-fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 29 publications
1
60
0
Order By: Relevance
“…A recent systematic analysis proposed a PFS-6 rate of 26% as the benchmark for historical comparisons. 14 Considering this benchmark, hydroxyurea, octreotide analogues, gefitinib, and erlotinib were deemed ineffective, 4,13,16 while anti-angiogenic drugs, including bevacizumab, vatalanib, and sunitinib showed potential activity, with PFS-6 rates of 37.5% to 64.3%. 11,14,17 -19 Interestingly, our data support a potential role of anti-angiogenic treatment in recurrent WHO grades II and III meningioma, as the most pronounced decrease of tumor growth rates was observed in patients put on bevacizumab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic analysis proposed a PFS-6 rate of 26% as the benchmark for historical comparisons. 14 Considering this benchmark, hydroxyurea, octreotide analogues, gefitinib, and erlotinib were deemed ineffective, 4,13,16 while anti-angiogenic drugs, including bevacizumab, vatalanib, and sunitinib showed potential activity, with PFS-6 rates of 37.5% to 64.3%. 11,14,17 -19 Interestingly, our data support a potential role of anti-angiogenic treatment in recurrent WHO grades II and III meningioma, as the most pronounced decrease of tumor growth rates was observed in patients put on bevacizumab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…9 A follow-up retrospective study of 35 patients with WHO Grade II and Grade III meningiomas showed 57% progression of disease at 6 months. 6 These results suggest that although hydroxyurea is generally well tolerated with limited toxicity, it appears to have very limited activity in tumor control. Investigators are currently looking at the role of hydroxyurea as an adjunct to other therapies, such as radiation or calcium channel blockers.…”
Section: Cytotoxic Agentsmentioning
confidence: 98%
“…Larger, more recent studies have also failed to demonstrate significant clinical efficacy. 6,9 In a recent large-scale trial that included 60 patients, progression of disease occurred in 65% of participants despite hydroxyurea therapy. 9 A follow-up retrospective study of 35 patients with WHO Grade II and Grade III meningiomas showed 57% progression of disease at 6 months.…”
Section: Cytotoxic Agentsmentioning
confidence: 99%
“…Pa-tients with these refractory tumors typically have a median overall survival of only 6-33 months. 9,38,56 Modern trials have looked at the possible utility of receptor tyrosine kinase (RTK) inhibitors. Gefitinib, erlotinib, and imatinib, which target platelet-derived growth factor receptor (PDGFR) and epidermal growth factor receptor (EGFR), respectively, have generally been ineffective for AM and MM.…”
Section: Chemotherapymentioning
confidence: 99%